Use of the Postural Assessment Scale for Stroke Patients in Determining Acute Care Discharge Recommendations. Issue 3 (July 2017) - Lesser, Melissa; Borst, Joseph; Dekerlegand, Jennifer
Abstract : Purpose/Hypothesis: Acute care therapists face many barriers that limit the use of screening tools including time constraints and lack of measures appropriate for use in this setting. The Postural Assessment Scale for Stroke patients (PASS) was developed to assess sitting, lying, and standing balance in persons who experienced a stroke. The StrokEDGE taskforce highly recommends the PASS for acute care, as it has excellent psychometric properties and clinical utility. This project used the PASS and the modified Rankin Scale (mRS) to assess mobility in persons with an acute stroke. The purpose of this quality improvement project was to assess the feasibility of physical therapists' use of the PASS as a screening tool to assist with discharge recommendations. Description: Data were collected during a 6-month period from the neurology floor of a 782-bed acute care hospital. Persons admitted with an acute stroke and had received a therapy evaluation were included in the cohort. The goal was to assess the PASS during the initial evaluation within 48 hours of hospital admission. Concurrent data collected during this time included mRS scores, Functional Independence Measure (FIM) transfer and ambulation scores, and therapist discharge recommendations. Results/Conclusions: One hundred fifty-three subjects, with a mean age of 64.5 ± 15.5 years, were included in this cohort. The mean PASS score was 19.7 ± 11.1, the mean mRS score was 3.7 ± 2.2, and the mean FIM scores was 2.7 ± 2.4 for transfers and 3.7 ± 1.6 for ambulation. Of the persons discharged home (N = 40), mean PASS scores were 31.8 for those recommended for home physical therapy (N = 14), 32.6 for an outpatient therapy recommendation (N = 12), and 34.9 for those requiring no therapy at discharge (N = 14). The mean PASS scores for persons with an acute rehabilitation recommendation (N = 100) was higher than those recommended for a skilled nursing facility/subacute rehabilitation (N = 13), 15.7 as compared with 9.5, respectively. Using the Pearson correlation coefficient, the PASS had a strong correlation with the FIM transfers at r = 0.90 and ambulation at r = 0.86, with a strong negative correlation to the mRS at r =−0.77 ( P < .001). Clinical Relevance: Acute care therapists should consider using the PASS to help guide clinical decision making and discharge recommendations for persons hospitalized with a stroke.